Assessment of Water-Migration-Gender Interconnections in Ethiopia - Färber, Lisa; Nagabhatla, Nidhi; Ruyssen, Ilse (Frontiers in Human Dynamics, 2022)
In recent years, water stress has affected Ethiopian people and communities through decreasing quantity, poor quality or poor service provisioning. Water stress is exacerbated by the impact of extreme events such as droughts and floods. For people exposed to water crisis – be it slow-onset water stress or in the context of water extremes - migration often forms an adequate adaptation strategy. Yet, the literature investigating the interlinkages between water stress and migration has largely ignored gendered effects. This paper contributes to the literature by assessing the nexus between water stress, migration, and gender in Ethiopia through a three-dimensional framework. Specifically, we investigate the influence of water stress-related dynamics on migration and gender disparities using a mixed tool approach. The analysis indicates that opportunities for migration as an adaptation strategy to deal with water stress are limited for Ethiopian women and girls. When having the chance to migrate to a more progressive region, they can benefit from other opportunities and options for education and emancipation. Current existing policy responses focus on durable solutions, including the creation of sustainable livelihoods, as well as the improvement of (access to) water, sanitation, and hygiene (WASH) facilities and water infrastructure. Gendered aspects seem to be gaining attention but still must be further strengthened in national and regional water governance plans and policies. We suggest that stakeholders could focus on long-term sustainable solutions and facilitate cooperation on all political levels to ensure that water governance is inclusive and gender-sensitive and support regulated migration pathways as an adaptation strategy. By implementing inclusive policies for water access, migration and gender, these actions can contribute to achieving the United Nations Sustainable Development Goals (SDSGs), in particular SDG #5 (gender equality), #6 (clean water and sanitation), #10 (reduced inequality), #13 (climate action and peace) and #16 (peace, justice and strong institutions).